Impact of TVET on Labour Market Outcomes and Women's Empowerment in Rural Areas: A Case Study from Cachar District, Assam. Issue 3 (December 2019) - Dey, Sagarika; Devi, Priyanka
This article evaluates the impact of technical and vocational education and training (TVET), a state-sponsored skills training programme, on the scope and quality of employment, income and women's empowerment among rural youths in Cachar district of Assam. Using a Heckman two-step approach, we find that training does enhance labour market outcomes of rural youths and has a particularly potent effect in securing women's empowerment. However, the study reveals that employment generation under the programme is heavily biased in favour of wage employment. It is therefore suggested that due attention should be given to promote self-employment ventures by ensuring credit availability and logistical support by tying up with financial institutions and other agencies. Besides, peripheral issues such as level of trainee satisfaction, workplace-related problems and skill mismatch in training and job requirements also need to be addressed for increasing programme efficacy.